Seroprevalence and Risk Factors Associated with Hepatitis E Virus Infection in Three Species of Pet Birds in Northwest China. (30th October 2014) - Cong, Wei; Meng, Qing-Feng; Shan, Xiao-Feng; Sun, Wu-Wen; Qin, Si-Yuan; Zhang, Xiao-Xuan; Huang, Si-Yang; Qian, Ai-Dong
Abstract : Hepatitis E virus (HEV), the causative agent of hepatitis E, has been reported in a wide variety of animals, including birds, but little is known of HEV infection in pet birds in northwest China. The objective of the present investigation was to examine HEV seroprevalence in three species of pet birds, namely, Eurasian siskin, Oriental skylark, and black-tailed grosbeak from Gansu. Serum samples collected from 685 pet birds from August 2011 to September 2012 were examined independently for the presence of antibodies against HEV. A total of 59 (8.31%) pet birds were tested positive for HEV antibodies by the commercially available enzyme immunoassay kits. Of these, the seroprevalence was diverse in different species pet birds; the most frequent level was 10.83% (39/360) in Eurasian siskin, followed by 6.57% (19/289) in Oriental skylark, and 2.29% (1/36) in black-tailed grosbeak. Age and collecting region of pet birds were the main risk factors associated with HEV infection. The present study firstly revealed the seroprevalence of HEV infection in three species of pet birds in northwest China, which provided the baseline data for taking comprehensive countermeasures and measures for effectively preventing and controlling HEV infection in birds.